Learning from the Armed Conflict Between India and Pakistan: Is Nuclear Weapons Necessary? - Siraj, Adnan; Khan, Shah Rukh; Jabbi, Yusupha (Faculty of Law, Universitas Jambi, 2025)
Background: The nuclearization of South Asia poses a long-term threat to the regional and global security. The long-standing rivalry between India and Pakistan is dangerously compounded by their opposing nuclear doctrines, and hence an analysis of their strategic stability is an imperative. Methodology: This study uses the methodology of comparative analysis and analysis of the nuclear postures of India and Pakistan in the context of modern deterrence theory and international law. The analysis rests on empirical evidence from past crises up to the time of the 2025 escalation to gain real world credibility of the doctrines. Objectives:The purpose of this paper is to dissect India's 'No First Use' policy vis-a-vis Pakistan's 'Full-Spectrum Deterrence' and first use ambiguity. It aims to examine how these contrary doctrines contribute to escalation and whether they comply with international legal norms. Findings: The analysis illuminates a critical